Implementation of the Value Added Tax Policy on the Delivery of Prepaid Credit and Starter Packs in Indonesia - Reshawna, Ray Abel; Hambali, Mohamad Luhur (Jurnal Administrasi dan Kebijakan Publik, 2025)
The issuance of Ministry of Finance Regulation (MoFR) No. 6/2021 has raised legal and administrative concerns among business actors. This study examines the implementation of Value-Added Tax (VAT) provisions governing the supply of prepaid credits and starter packs by Next Tier Distributors, identifies key factors influencing implementation, and highlights a significant misalignment between field practices in VAT collection and the regulation’s original policy objectives. Using a qualitative approach, data were collected through in-depth interviews with business actors and a review of relevant literature. The findings reveal that MoFR 6/2021 has created regulatory uncertainty among Taxable Persons, prompting some businesses to strategically choose the Next Tier Distributor designation to avoid the administrative and financial burdens associated with VAT collection. The inconsistency between the VAT Law and MoFR 6/2021 has also produced regulatory dualism, leading to confusion and reduced compliance. Supporting factors for implementation include the availability of educational materials from the Directorate General of Taxes, while inhibiting factors are regulatory uncertainty and partial non-compliance. This study recommends aligning MoFR 6/2021 with the VAT Law, simplifying distribution tiers, and strengthening outreach to Taxable Persons.